Rebranding the Cakru Jember Village Instagram Account as Exhibition Means of Village Cultural and Economic Tourism Potential: Rebranding Akun Instagram Desa Cakru Jember Sebagai Sarana Ekshibisi Potensi Wisata Budaya dan Ekonomi Desa - Fauzan Fahmi Baswedan; Aisa Fadhilatul Istiqomah; Ershazkiya Raudlatishafa; Hudayya Dinnul Islami Chasih; Dita Atasa; Dita Megasari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Cakru Village in Jember Regency, Indonesia, has great economic and cultural potential but has not been optimally utilized. Data collection of MSMEs from various hamlets shows the diversity of local economic sectors. This activity aims to increase public awareness of this potential through socialization and rebranding of social media. This program involves preparation by means of observation and interviews, implementation of socialization, and evaluation using pre-test and post-test. The results of the pre-test showed that public knowledge of village potential was still low. After the socialization, there was a significant increase in awareness of village potential from the Cakru Village community who participated in the socialization, as much as 90%, especially regarding the potential of MSMEs and Japanese protection tourism. In addition, the rebranding of Instagram from the old account to the new account @discoverycakru.id successfully introduced MSMEs and historical sites with a focus on innovative content. This program shows the effectiveness of social media in increasing visibility and support for the local economy, as well as introducing the unique culture of Cakru Village to a wider audience.